An Analysis of The Influence of Audit Capacity Stress, Size of The Company and The Independence of Audit Committee Upon Audit Quality at Company Banking Listed on BEI (Indonesia Stock Exchange) for The Period of 2012 – 2016 - Asna Manulang (The Accounting Journal of Binaniaga, 2018)
The objective of this research is to find out and to analyze the influence of audit capacity stress, size of the company and the independence of audit committee upon audit quality (empiric study at company banking listed on BEI period of 2012 – 2016). The result of this research has shown that audit capacity stress, size of the company and the independence of audit quality had not significantly influenced audit quality of company banking listed on BEI.Keywords: Audit Capacity Stress, Size of the company, The Independence of Audit Committee, Audit Quality.